Determinants of Hypertension Incidence in the Work Areas of the Bone and Barru District Health Centers in 2022 - Ida Leida Maria; Andi Selvi Yusnitasari; Clement Lifoia; A. Tiara Aurelia Annisa; Sri Mulyani (Media Kesehatan Masyarakat Indonesia, 2022)
Hypertension is often called the silent killer because it does not show any symptoms. Hence, not all people with hypertension are aware that they suffer from a chronic condition that can cause degenerative diseases, to death. Hypertension is a problem that is often found in society, both in developed and developing countries, especially in Indonesia. The purpose of this study was to determine the factors associated with the incidence of hypertension in the work area of Dua Boccoe Health Center and Blue Health Center of Bone Regency and Padongko Health Center and Palakka Health Center of Barru Regency, with a high prevalence of hypertension cases in Bone Regency (29.33%) and Barru Regency (33.59%). The type of research used is observational with cross-sectional design with a total of 356 respondents. Data were processed using the SPSS program with chi-square analysis and logistic regression. The results of the study based on the chi-square test showed that there was a relationship between the variables of age, education level, family history of hypertension, smoking, and stress with the incidence of hypertension (p<0.05) and there was no relationship between the variables of sex and physical activity with the incidence of hypertension (p>0.05). Furthermore, based on the logistic regression test, respondents were at a 6.5 times greater risk of developing hypertension if they had stress risk factors. Therefore, respondents are expected to carry out regular health checks and maintain a healthy lifestyle to control risk factors for hypertension.